Uruguayan rock in the eighties: traditions unexpectedly reinvented - Delgado, Leandro (2014)
Evidences of musicians from the Eighties indicate that they played music in the same stages than musicians of the prior generation. Such a contact – that was conflictive occasionally – allowed the new musicians to build an idiosyncratic generational identity, and challenges the idea that the rock of the Eighties in Uruguay would have been born without artistic parents, as stated in the musical critic reviews of the time. This article examines, first, how critical reviews and chronicles contributed to the building of an eloquent discourse for the new youth subculture. Second, it questions the idea of orphanhood describing how musicians and journalists rejected and resignified certain elements of existing cultural tradition thus making the rock from the Eighties the defining cultural element of the decade.